Cutaneous dermal non‐neural granular cell tumor is a granular cell dermal root sheath fibroma. (23rd March 2017) - Fernandez‐Flores, Angel; Cassarino, David S.; Riveiro‐Falkenbach, Erica; Rodriguez‐Peralto, José Luis; Fernandez‐Figueras, Maria Teresa; Monteagudo, Carlos
Abstract : Dermal non‐neural granular cell tumor (NNGCT) was first described in 1991 as an S100‐negative polypoid non‐melanocytic tumor. Although originally introduced in the literature as a primary cutaneous tumor, it was later emphasized that such qualification could not be held until the line of differentiation was clarified. It was also demonstrated that not all cases were polypoid. In the current study we try to further characterize this entity by presenting 5 cases of NNGCT. As expected, not all of them were polypoid. The ages of the patients varied from 10 to 43 (mean age 22). They all were composed of S100‐negative granular cells with variable atypia and mitotic figures. None of them recurred in follow‐up of up to 12 years (mean 8.2 years). We found evidence of folliculocentricity in 4 cases (in 1 case, this feature could not be investigated because the biopsy was a small shave specimen), that is, tumors were always surrounding, embedding, or following a hair follicle. In some occasions, such features were better demonstrated by immunohistochemistry against the arrector pili muscle. Our cases showed intense immunoexpression of CD10 and CD68. We conclude that NNGCT is morphologically related to the hair follicle and we believe that it is a granular cell dermal root sheath fibroma.